Constitutional role and powers of the modern monarchy in democratic government: the Malaysian experience - Mokhtar, Khairil Azmin (IIUM Press, 2009)
The so-called figurehead monarch of Westminster-type constitutions, where the positions of head of state and the head of the government are held by different persons, needs to be appreciated in light of the substantive and discretionary powers exercised by such heads of state in the maintenance of a just and democratic system of government. In the Malaysian Constitutional framework the position of the Yang di-Pertuan Agong and the Sultans are actually a modern one as much as democracy itself is, and an interesting comparison may be made with nations with similar but non-hereditary heads of state. Instances and events referred in the paper illustrate the practical significance of the Malaysian monarchy. Within Malaysian constitutional and social contexts the function of monarchy goes beyond symbolic roles because it have important responsibility and duties to protect and preserve democratic ideals underpinning the philosophy of this nation. As heads of the state the monarchs is constitutionally bound to ensure the governments are functioning within parameters set out in the Constitution and to protect interest of the people regardless of their religion and political affiliation. The Malay rulers, as stated by His Highness Raja Nazrin, must adapt to this changing circumstances. Though the institution is steeped in tradition it must reflect a contemporary outlook. This is admitted by His Highness Raja Nazrin Shah in his speech title The Monarchy in Contemporary Malaysia that 'Changes, when required, have to be addressed and accommodated to suit the temper of times.' The monarchs in Malaysia has proven its resilience by adapting itself to the changing needs and aspirations of the Malaysian society from time to time, and at the same time manage to preserve its traditional role and its tradition. This is an important factor for its success and perseverance.